The Role of Artificial Intelligence (AI) and its Benefits in Digital Marketing Strategy - Apriani, Ari; Sani, Indra; Kurniawati, Lia; Prayoga, Rahmat; Panggabean, Helena Louise (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the role of artificial intelligence (AI) in digital marketing strategy and its benefits. AI is a technology that enables computers or machines to process information and produce outcomes similar to human thought processes. The implementation of AI in marketing can enhance personalization, predictive analytics, chatbots and customer service, content optimization, ad targeting and optimization, and marketing automation. Understanding customer behavior, strategic decision making, tactical marketing, ethical and responsible AI, integration with other technologies, and collaboration with AI providers and start-ups are all best practices for incorporating AI in marketing initiatives. The search results emphasize the anticipated importance of AI solutions in marketing decision-making across the five stages of the marketing process, which include analysis, strategy, tactics, customer interactions, and value proposition creation. With enhanced customization, integration with other technologies, and a stronger emphasis on ethical and responsible AI, the future of AI in marketing analytics is bright. To effectively exploit the power of AI, businesses should invest in AI knowledge, emphasize ethical and responsible AI, focus on customer privacy and data protection, embrace new technologies, and collaborate with AI suppliers and start-ups.